Legal Analysis of the Granting of Assimilation Rights to Inmates (A Study at the Class II A Detention Center in Kendari) - Maharani, Rizka; L., St. Fatmawati; Basoddin, Basoddin (International Journal of Management and Education in Human Development, 2025)
This study aims to determine 1) how human rights are implemented through assimilation for female inmates and 2) the factors that hinder its implementation. This research was conducted empirically, by studying various books and laws and regulations related to the material for this thesis. Data collection techniques in this study were field research and library research to obtain data related to the title of this thesis. The data were then processed and analyzed using qualitative descriptive methods to describe the chronology of the cases that occurred. The results of this study conclude that inmate rehabilitation is part of the law enforcement process. The correctional system is organized to shape correctional inmates into human beings who are aware of all mistakes, improve themselves, and do not repeat criminal acts so that they are accepted by the community and can live normally, like society in general, as good and responsible citizens. In order for assimilation to be obtained, it is mandatory to fulfill general and specific requirements, namely having behaved well during the prison term, actively participating in the development program, and having carried out 1/2 of the prison term, and this applies to inmates of general crimes. As well as 2/3 of the sentence for inmates of special crimes, for example, drugs and transnational crimes, in this case, in every implementation of assimilation, obstacles will be found that become inhibiting factors for the implementation of the assimilation program. Apart from the existing statutory regulations, other things also come from external and internal factors, both from the inmates themselves and other things outside themselves